Analisis Kandungan CNPK dari Hasil Pemanfaatan Sampah Sisa Makanan Menjadi Pupuk Organik Cair (POC) - Vivin Setiani; Dinda Maya Kristina; Livia Armesta; Aisyah Choirul Amien; Moch. Defrianto (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Food waste was the largest generation of all types of waste and one of the problems in waste management in Indonesia. One alternative to reduce the generation of food waste is to use food waste to become Liquid Organic Fertilizers (LOF). In this study, the fermentation of food waste into POC through a 21-day. The fermentation is carried out anaerobically. A variation of this research consists of adding Effective Microorganism (EM4) solution as a biostater in the manufacture of LOF. The addition of EM4 solution in this study consisted of variation 1 (5 mL EM4 solution), variation 2 (10 mL EM4 solution), variation 3 (15 mL EM4 solution), and variation 4 (0 mL EM4 solution). Chemical analysis carried out on the quality of LOF consists of Carbon, Nitrogen, Phosphorus, and Potassium content. The results of this study indicated that the highest carbon and potassium content was in variation 4 (without EM4 solution), while the highest nitrogen and phosphorus content was in variation 3 with the addition of 15 mL EM4 solution. All variations in this study did not meet the standard values for carbon, nitrogen, phosphorus, and potassium in content of liquid organic fertilizer.